Digital Pressure Meter Design to Calibrate A Sphygmomanometer Unit Equipped with Data Calibration Recording to External Memory - Moch. Prastawa Assalim Tetra Putra; Yuliantri Selvi Anugrahni; Kamilu O. Lawal (Jurnal Teknokes, 2022)
A sphygmomanometer is a medical device used to non-invasively measure arterial blood pressure. To ensure the accuracy of this device, it must be calibrated. The equipment used to calibrate this tool is a Digital Pressure Meter (DPM). This study aims to build a DPM device equipped with SD card storage. The device runs on the MPX5050GP sensor, the measurement results are displayed on a 16x4 Liquid Crystal Display Character (LCD) This device is also equipped with a leakage test timer, and data storage on the SD Card will be displayed in Notepad (txt) form. The variables measured in data collection were positive pressure and leakage test. The DPM feature of the Rigel Medical UNI-SiM Calibrator is used as the gold standard tool for comparing device accuracy. From the comparison with the gold standard, the smallest error is 0.00% and the largest error is 0.11% on the positive pressure variable and the error is 0.26. % on the leak test variable. The GEA Medical MI-2001 Mercury Sphygmomanometer was used as an under test standard with the smallest measurement error of 0.00% and the largest error of 0.81% and the value of the leak test error compared to the DPM Module which was 0.9%. Data storage is still manual. Automating data retrieval and transfer to computers or other digital gadgets will make it easier for officers who use this DPM tool. The next research will be good using web applications like data storage and processing.